0863 Age-categorized Trends In Self-reported Sleep Duration For The Non-institutionalized U.s. Civilian Population From 2004-2013: Considerations Of Racial/ethnic Variations. (27th May 2020) - Christina, M; Bubu, O M; Donley, T; Blanc, J; Oji, E; Turner, A D; Mbah, A K; Williams, N J; Youngstedt, S; Shochat, T; Azizi, S A; Osorio, R S; et al.
Abstract: Introduction: We examined age-categorized trends in self-reported sleep duration using data from the National Health Interview Survey (NHIS) 2004-2013 and explored how these trends may vary based on individuals' race/ethnicity. Methods: Study participants were aged 18-85 (N=258, 158). Sleep duration within a 24-hour period on average was categorized as ≤ 6hrs (short-sleep), 7-8 hours (adequate-sleep), and ≥ 9hrs (long-sleep). Age was categorized as 18 - <26, 26 - <65 and 65 - 85. Racial categories included non-Hispanic Whites (NHW), Blacks/African Americans (AAs) and Hispanics. Adjusted multinomial logistic regression models examined trends in self-reported sleep duration across age-categories and assessed race/ethnic differences in these trends. Results: Mean sleep duration (hrs.) across all years was 7.4, 7.0, and 7.5, for ages 18 - <26, 26 - <65 and 65 - 85, respectively and was relatively stable from 2004-2013. However, compared to individuals ages 18 - <26, those categorized as ages 26 - <65 were 55% more likely to be short sleepers while those ages 65 - 85 were 20% less likely to be short sleepers ( P < .001 for all). Mean sleep duration was 7.2hrs, for NHW and 7.1hrs for AAs and Hispanics, and showed increasing trend toward short sleep beginning in 2007 through 2013 ( P <.01 for trend). In the age 18 - <26 category, compared to whites, blacks and Hispanics were 35% and 29% more likely to be short sleepers, respectively. In the age 26 - <65 category, compared to whites, blacks and Hispanics were 35% and 21% more likely to be short sleepers, respectively. In the age 65 - 85 category, compared to whites, blacks were 19% more likely to be short sleepers ( P < .001 for all). Conclusion: Continued surveillance of population-level sleep trends among minority populations is essential as growing race/ethnic (age specific) disparities in self-reported sleep duration may have consequences for racial/ethnic health disparities. Support: NIH/NIA/NHLBI (L30-AG064670, CIRAD P30AG059303 Pilot, T32HL129953, R01AG056531, R25HL105444, R25NS094093, K07AG05268503, R01HL142066, K23HL125939)